2007
DOI: 10.1590/s1676-06032007000200011
|View full text |Cite
|
Sign up to set email alerts
|

Variação temporal no sítio de vocalização em uma comunidade de anuros de Botucatu, Estado de São Paulo, Brasil

Abstract: Um estudo da variação temporal no sítio de vocalização de uma comunidade de anuros foi realizado em uma poça permanente, entre outubro de 1996 e fevereiro de 1998, em Rubião Jr. município de Botucatu, São Paulo. Foram registradas 14 espécies de anuros pertencentes às famílias Hylidae, Leptodactylidae, Leiuperidae e Bufonidae. A comunidade apresentou um maior número (n = 6) de espécies de ocorrência acidental (n < 20%) e maior riqueza de espécies e número de machos em atividade de vocalização nos meses quent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
2
9
0
11
Order By: Relevance
“…Even though the species may congregate for breeding throughout the year, with decrease in abundance on nights with temperatures below 15°C (Brassaloti et al, 2010), we recorded calling activities at even lower temperatures in Nova Alvorada do Sul (~8-15°C). All males were calling perched over shrubs and aquatic vegetation, in agreement with Jim (1980), but Melo et al, (2007) also found males calling on the floor.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Even though the species may congregate for breeding throughout the year, with decrease in abundance on nights with temperatures below 15°C (Brassaloti et al, 2010), we recorded calling activities at even lower temperatures in Nova Alvorada do Sul (~8-15°C). All males were calling perched over shrubs and aquatic vegetation, in agreement with Jim (1980), but Melo et al, (2007) also found males calling on the floor.…”
Section: Discussionsupporting
confidence: 88%
“…Considering the new records, males of H. caingua were only found in calling activities under low temperatures, which reinforces the hypothesis of adaptation to low temperatures (Melo et al, 2007). Even though the species may congregate for breeding throughout the year, with decrease in abundance on nights with temperatures below 15°C (Brassaloti et al, 2010), we recorded calling activities at even lower temperatures in Nova Alvorada do Sul (~8-15°C).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations